The influence and role of healthcare personnel in the football industry - Gülenç, Barış; Kuyucu, Ersin; Erdil, Mehmet Emin (Peter Lang AG, 2017)
[Abstract Not Available]
Keywords: Healthcare Personnel; Football Industry; Influence